85.9k views
1 vote
Identify the equivalent expression for each of the expressions below

Identify the equivalent expression for each of the expressions below-example-1
User Rhernando
by
5.4k points

1 Answer

4 votes

Answer: The answer is (c)
x^(1)/(2)+3.

Step-by-step explanation: We are given to identify from the options that which expression is equivalent to the expression below:


E=√(x)+3.

We know that


√(x)=x^(1)/(2).

Therefore, the given expression becomes


E\\\\=√(x)+3\\\\=x^(1)/(2)+3.

Thus, (c) is the correct option.

User Taalib
by
6.3k points